Linking urban consumers and rural farmers in India: A comparison of traditional and modern food supply chains - Minten, Bart; Reardon, Thomas; Vandeplas, Anneleen (International Food Policy Research Institute, 2009)
Food supply chains are being transformed in a number of developing countries due to widespread changes in urban food demand. To better anticipate the impact of this transformation and thus assist in the design of appropriate policies, it is important to understand the changes that are occurring in these supply chains. In a case study of India, we find that overall urban consumption is increasing; the urban food basket is shifting away from staples toward high-value products; and modern market channels (modern retail, food processing, and the food service industry) are on the rise. We document differing practices in traditional and modern food supply chains and identify an agenda for future research.